NIR-laser-induced selective rotamerization of hydroxy conformers of cytosine - Lapinski, Leszek (2010)
The relative populations of two amino-hydroxy conformers of cytosine, differing in rotation of the OH group by 180°, were selectively and repeatedly manipulated with narrowband, near-infrared laser light. For cytosine monomers isolated in a low-temperature Ar matrix, laser irradiations at 7013 cm−1 and at 7034 cm−1 were found to induce effective transformations of the two conformers into each other.